The effect of high temperature climate on the hydration status of the Sudanese top league football players (Journal of the College of Basic Education, 2022)
The study aimed at identifying the effect of high temperature climate on the hydration status of the Sudanese top league football players. A descriptive approach was used , and the study sample included 50 of the Sudanese top league football players who were randomly selected. Questionnaires were used for data collection. Important results were that 60% of the players didn’t drink plenty of fluids one day ahead of the match, and 46% didn’t drink during exercise, and also 54% didn’t have instructions to drink plenty of fluids before the exercise, and also only 20% of the players were weighed by the coach before and after exercises. Moreover it was also found that only 10% of the players used rehydrating fluids during exercise. And finally reduced urine volume was the most common symptom of dehydration, since 92% of the players had it.Important recommendations were: To raise awareness about the importance of proper hydration among the players, the staff, and others who are responsible for them, To implement the FIFA instructions regarding playing in hot climates, that is to pause a match allowing time for fluid replacement and rehydration, and finally to use this study for future visions along with other studies concerning hydrations and hot climates, with special regards that the football world cup 2022 is going to be in Qatar.